Factors influencing the consumers’ intention to use environmental friendly products / Nor Baeyah Jahaya and Nurhidayah ‘Aliaa Che Zulhaimee - Jahaya, Nor Baeyah; Che Zulhaimee, Nurhidayah ‘Aliaa (Faculty of Business and Management, 2014)
The title of this research is Factors Influencing Consumers’ Intention to Use Environmental Friendly Products. The defendant variable for this research is intention to use environmental friendly products. In this research, there are six independent variables that link with the defendant variable. The six independent variables are perceived cost, perceived quality, environmental attitude, social influence, trust and health awareness. For the data collection, questionnaire was used by the researchers. The researchers distributed the set of questionnaires to respondents in the shopping complex around Melaka. In conducting the research, the Statistical Package for Social Science (SPSS) version 21.0 was used to analyzed the data. Results showed the five independent variables which are perceived cost, perceived quality, environmental attitude, trust and health awareness influencing the consumers’ intention to use environmental friendly products. But only one independent variable which is social influence does not influence the defendant variable. All the five independent variables have significant relationships that influence the consumers’ intention to use environmental friendly products.